2012
DOI: 10.1111/j.1468-3083.2012.04512.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual behaviours, knowledge and attitudes regarding safe sex, and prevalence of non‐viral sexually transmitted infections among attendees of youth clinics in St. Petersburg, Russia

Abstract: Background  Adolescents and young adults are at increased risk of sexually transmitted infections (STIs). Knowledge of STI prevalence and risk factors are essential tools to elaborate preventive strategies. However, internationally reported studies on epidemiology of STIs among the youth in Russia are mainly lacking. Objectives  To ascertain sexual behaviours, knowledge and attitudes about safe sex and prevalence and correlates with STIs in attendees of youth clinics in St. Petersburg, Russia. Methods  A total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Some studies have suggested that mycoplasma and ureaplasma can contribute to genitourinary infection and infertility ( 13 14 15 16 17 18 ). However, studies have only investigated the prevalence of Mycoplasma genitalium in adolescents ( 19 20 ). Therefore, we investigated the prevalence of Mycoplasma hominis , M. genitalium , Ureaplasma parvum , and Ureaplasma urealyticum .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that mycoplasma and ureaplasma can contribute to genitourinary infection and infertility ( 13 14 15 16 17 18 ). However, studies have only investigated the prevalence of Mycoplasma genitalium in adolescents ( 19 20 ). Therefore, we investigated the prevalence of Mycoplasma hominis , M. genitalium , Ureaplasma parvum , and Ureaplasma urealyticum .…”
Section: Introductionmentioning
confidence: 99%
“…В ходе исследования L. Manhart и соавт. (2007) пришли к выводу, что выявляемость M. genitalium выше у подростков негроидной расы, а также лиц, ведущих активную сексуальную жизнь [25][26][27]. первые данные об этиологической роли M. genitalium в развитии воспалительного процесса в цервикальном канале были опубликованы в 1997 г. японскими учеными M. uno и соавт., обнаружившими данный микроорганизм у 5 из 57 женщин с цервицитом, при этом ни у одной из 79 здоровых женщин он не был выявлен [28].…”
Section: роль микоплазм в развитии патологических процессов урогенита...unclassified
“…Por se tratar de um critério de exclusão, indivíduos portadores do vírus não participaram da amostragem do presente estudo. Apesar de ser isolado em indivíduos homossexuais HIV negativos, a maioria dos achados foi relacionada a indivíduos infectados pelo vírus do HIV (CORDOVA; CUNHA, 2000;CUNHA, 2002;HUSSAIN et al, 1999 (BELKUM et al, 2001;DESSÌ et al, 2005;FRAGA et al, 2012;KOCH et al, 1997;SHIPITSYNA et al, 2013 A diferença encontrada nos valores de detecção deve-se às características das populações estudadas bem como da metodologia aplicada. É consenso entre os diferentes pesquisadores (ABELE-HORN et al, 1996;AMIRMOZAFARI et al, 2009;BÉBÉAR et al, 1997) que as técnicas de biologia molecular como a PCR convencional e a qPCR são mais sensíveis do que o isolamento de microrganismos fastidiosos como micoplasmas (AMIRMOZAFARI et al, 2009;SONAWANE;TRIPATHI, 2013).…”
Section: Relação Da Concentração Das Citocinas Il-1β E Il-6 E Os Difeunclassified